Potential and Implementation of Halal Tourism During the Covid-19 Pandemic in Semarang City - Hermintoyo Muhammad (EDP Sciences, 2021)
Semarang is an attractive and quite a lot of tourist destinations. This shows that the city of Semarang has potential in the implementation of tourism. In general, the tourism potential in the city of Semarang can be divided into natural tourism and cultural tourism. Tourism in the city of Semarang is feasible to implement halal tourist destinations. The definition of halal does not refer to religious or religious tourism but provides comfort for tourists who are predominantly Muslim. Halal tourism has been launched by the MUI since 2015. This declaration is expected to balance the implementation of halal tourism because the majority of the population is Muslim. Tourism potential During the COVID-19 pandemic, halal tourism in Semarang City, must comply with strict health protocols if tourism in Semarang City is to be opened. Data collection in this halal tourism research. Using the observation method with direct interview techniques and questionnaires via online / WA. The classified data is then analyzed qualitatively.